Shine a (night)light - Bargain, Olivier,Vincent, Rose Camille,Caldeira, Emilie (IZA - Institute of Labor Economics, 2024)
Decentralization, championed by international institutions, has been one of the most prominent public sector reforms of the last decades, particularly in sub-Saharan Africa. To date, few studies propose a quasi-experimental evaluation of its capacity to contribute to local development. We exploit the phase-in of decentralization at the commune level in Burkina Faso. We use satellite information on night-time light density as a proxy for local development levels, which has the advantage of being measured and comparable over time and space. The communes that were decentralized first can be compared to the others after the reform relative to the pre-reform situation. The difference-in-difference approach includes commune fixed effects and inverse propensity score reweighting to account for time-varying differences across communes. We find a positive impact of decentralization on the night-light intensity trends of the early-decentralized communes. This is supported by alternative measures (remote sensing of built-up settlements and a welfare index), which shows the possibly broader scope of decentralization gains. We show that decentralization did not lift all boats: only the communes with the ability to generate own-source revenues benefited from effective decentralization.
https://www.iza.org/publications/dp/17459/shine-a-nightlight-decentralization-and-economic-development-in-burkina-faso
Keywords: Graue Literatur; decentralization; economic development; local development; Africa; Burkina Faso